EVALUATION OF ULTRASONOGRAPHY AS AN ADJUNCT FOR DIAGNOSIS OF DENGUE FEVER AMONG CHILDREN: A PROSPECTIVE STUDY. - Shamikumar, R. P.; Mohammed, Syed; Ashika Banu M; Janani M. Z; Srinivasan, Chethan; Ananya, T. S. L. (Student’s Journal of Health Research Africa, 2023)
Introduction: This study aims to evaluate the role of ultrasonography (USG) for early diagnosis of clinically suspected dengue fever before it becomes serologically positive and the usefulness of USG in predicting the severity of the disease. Methods: Prospective observational study conducted at a tertiary care hospital from April 2020 to March 2021, 70 cases of clinically suspected dengue within the age group of 6 months to 15 years resenting with fever for less than 5 days underwent whole abdomen and chest ultrasonography. For seropositive cases, ultrasonography findings and their utility in early diagnosis and prediction of disease severity were analyzed along with their correlation to the clinical and laboratory profiles. Results: 75.8% had primary dengue and 24.2% had secondary dengue. 94% of cases demonstrated ultrasonography features suggestive of dengue-like hepatomegaly (81%), ascites (63.8%), splenomegaly (56.9%), gall bladder wall thickness (46.6%), Cholecystitis (44.8%) and Pleural effusion (41.4%). Ascites and pleural effusion correlated well with clinical severity (p<0.05). Ascites also had a significant correlation with increased hematocrit (p=0.040) and thrombocytopenia (p=0). A significant correlation was observed between pleural effusion with decreased platelet count ((p=0.004) and decreased serum sodium levels (p=0.044). Gall bladder wall thickening >5mm correlated well with disease severity. USG showed 94.3% sensitivity, 16.67% specificity, and 81.43% of diagnostic accuracy in the seropositive cases of this study. Conclusion: Ultrasonography is useful not only as an adjuvant for early diagnosis of Dengue fever but also as a marker of disease severity.